Spatial Genetic Structure in Seed Stands of Pinus arizonica Engelm. and Pinus cooperi Blanco in the State of Durango, Mexico. Issue 2 (5th April 2018) - Friedrich, Saskia C; Hernández-Díaz, José C; Leinemann, Ludger; Prieto-Ruíz, José A; Wehenkel, Christian
Abstract: Spatial genetic structure (SGS) characterizes the geographical distribution of genetic variation. Pinus arizonica and P. cooperi are two of the most important timber tree species in Mexico. Certified seed stands of these species are needed to increase productivity and recover degraded areas. In the present study, we analyzed neutral and putatively adaptive AFLPs to examine the SGS in 12 natural seed stands of P. arizonica and P. cooperi at local (within the seed stands) and large scales (among the seed stands). Since these pine species are wind pollinated, widespread, and often occur at high population densities, we did not expect to find any SGS at the fine scale or significant differences in the SGS of the two species. At the fine scale, we observed highly significant spatial genetic autocorrelation for both species in only two of the 12 seed stands. At the large scale, we observed significant spatial structure, which may be the result of isolation by distance. We recommend establishing a fine-meshed network of seed stands, with maximal distances of 9–18 km between them to prevent greater loss of local genetic structure.